Limb immobilization alters functional electrophysiological parameters of sciatic nerve - Alves,J.S.M. (2013)
Immobilization, used in clinical practice to treat traumatologic problems, causes changes in muscle, but it is not known whether changes also occur in nerves. We investigated the effects of immobilization on excitability and compound action potential (CAP) and the ultrastructure of the rat sciatic nerve. Fourteen days after immobilization of the right leg of adult male Wistar rats (n=34), animals were killed and the right sciatic nerve was dissected and mounted in a moist chamber. Nerves were stimulated at a baseline frequency of 0.2 Hz and tested for 2 min at 20, 50, and 100 Hz. Immobilization altered nerve excitability. Rheobase and chronaxy changed from 3.13±0.05 V and 52.31±1.95 µs (control group, n=13) to 2.84±0.06 V and 59.71±2.79 µs (immobilized group, n=15), respectively. Immobilization altered the amplitude of CAP waves and decreased the conduction velocity of the first CAP wave (from 93.63±7.49 to 79.14±5.59 m/s) but not of the second wave. Transmission electron microscopy showed fragmentation of the myelin sheath of the sciatic nerve of immobilized limbs and degeneration of the axon. In conclusion, we demonstrated that long-lasting leg immobilization can induce alterations in nerve function.